Efficacy and safety of combined vs. single renin-angiotensin-aldosterone system blockade in chronic kidney disease - Mona A. Abdelrahman; Ashraf Genina; Amira S. A. Said; Mohamed E. A. Abdelrahim (Medicine Science, 2016)
Hypertension and proteinuria are well-known predictors of chronic kidney disease (CKD) progression. Therapeutic interventions have different magnitude of albuminuria and hypertension. This study was designed to evaluate the efficacy and safety of combined vs. single renin-angiotensin-aldosterone system (RAAS) blockade in chronic kidney disease. Forty (28 female) patients with chronic kidney diseases were collected from nephrology outpatient clinic, internal medicine department, Beni Suef University hospital. They were divided randomly into 2 groups. Group A was 24 (20 females) patients treated with Enalapril, as angiotensin converting enzyme inhibitor (ACE-I) alone. Group B was 16 (8 females) patients treated with combination of Enalapril and Irbesartan, as angiotensin receptor blocker (ARB). All patients were subjected to full history taking; thorough clinical examination; certain laboratory tests and renal function tests at the start of the study, 1.5 and 3 months later. Proteinuria, urinary albumin/creatinine ratio (UACR), systolic blood pressure (SBP) and glomerular filtration rate (GFR) were significantly (p [Med-Science 2016; 5(3.000): 751-7]